2016
DOI: 10.1615/plasmamed.2017019830
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Biocidal Activity of Dielectric Barrier Discharge Air Jet with Misting

Abstract: Two nearly identical plasma jet-like systems with water misting were investigated for effective pathogen inactivation regimens on Escherichia coli in atmospheric conditions. Although the electrode construction is quite similar, we show that the concentration of active species generated at the exit of the discharge is quite different, and inactivation of bacteria by this treatment also varies. Inactivation and production rates of hydrogen peroxide, nitrate, and nitrite in liquid were higher when a single quartz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Plasma treatment of seeds can increase their germination rates and efficiencies and plasma can enhance plant growth. Seeds, food, and food processing tools can be protected from or decontaminated of fungi or bacteria . Furthermore, plasma chemistry may help to produce fertilizers or to enable sustainable material life cycles with its unique nonthermal character …”
Section: Introductionmentioning
confidence: 99%
“…Plasma treatment of seeds can increase their germination rates and efficiencies and plasma can enhance plant growth. Seeds, food, and food processing tools can be protected from or decontaminated of fungi or bacteria . Furthermore, plasma chemistry may help to produce fertilizers or to enable sustainable material life cycles with its unique nonthermal character …”
Section: Introductionmentioning
confidence: 99%
“…The acidification of the mist is caused by the reactions of the RNS generated by the discharge with water to produce nitric and nitrous acids, as shown in reactions ( 22) and ( 24). [12,14] The conductivity is elevated to 770 and 1207 μS/cm for PAWM and PAHM, respectively, due to the accumulation of positive and negative ions in the mist during the discharge. The conductivity of PAHM is more significantly enhanced than PAWM, indicating a larger number of charged particles produced by PAHM.…”
Section: Ph and Conductivitymentioning
confidence: 99%
“…The bactericidal results of F I G U R E 6 pH and conductivity under different conditions PAWM in this study are not as effective as reported in other literature. [7,12,36] In previous studies, the activated water is mixed directly with the bacterial solution to make full use of the active substances, which is not applicable for logistics sterilization. In this study, the PAWM ejected by the DBD nozzle does not penetrate all the way into the bacterial solution, partially spreading into the air.…”
Section: Sterilization Performancementioning
confidence: 99%
“…The mspDBD system previously described by the author, was used. 11,14 A hollow square was used to mount seven high-voltage electrodes and six ground electrodes at 45º relative to their cross-sectional centers, and ~ 1 mm away from each other as measured from their outer diameters (Figs. 1-3).…”
Section: B Plasma System Designmentioning
confidence: 99%
“…11 The design of the electrode grid was borrowed from 12,13 we applied pulses of 3 μs duration and 26 kV amplitude at 1000 Hz to a grid of wires in which the high-voltage and ground wires alternate and the high-voltage wire was supply limitations. 14 and sugar content) of bananas.…”
Section: Introductionmentioning
confidence: 99%